Medicines coverage and community-based health insurance in low-income countries - Wagner Anita K; Ntaganira Joseph; Ross-Degnan Dennis; Vialle-Valentin Catherine E (BMC, 2008)
Abstract Objectives The 2004 International Conference on Improving Use of Medicines recommended that emerging and expanding health insurances in low-income countries focus on improving access to and use of medicines. In recent years, Community-based Health Insurance (CHI) schemes have multiplied, with mounting evidence of their positive effects on financial protection and resource mobilization for healthcare in poor settings. Using literature review and qualitative interviews, this paper investigates whether and how CHI expands access to medicines in low-income countries. Methods We used three complementary data collection approaches: (1) analysis of WHO National Health Accounts (NHA) and available results from the World Health Survey (WHS); (2) review of peer-reviewed articles published since 2002 and documents posted online by national insurance programs and international organizations; (3) structured interviews of CHI managers about key issues related to medicines benefit packages in Lao PDR and Rwanda. Results In low-income countries, only two percent of WHS respondents with voluntary insurance belong to the lowest income quintile, suggesting very low CHI penetration among the poor. Yet according to the WHS, medicines are the largest reported component of out-of-pocket payments for healthcare in these countries (median 41.7%) and this proportion is inversely associated with income quintile. Publications have mentioned over a thousand CHI schemes in 19 low-income countries, usually without in-depth description of the type, extent, or adequacy of medicines coverage. Evidence from the literature is scarce about how coverage affects medicines utilization or how schemes use cost-containment tools like co-payments and formularies. On the other hand, interviews found that medicines may represent up to 80% of CHI expenditures. Conclusion This paper highlights the paucity of evidence about medicines coverage in CHI. Given the policy commitment to expand CHI in several countries (e.g. Rwanda, Lao PDR) and the potential of CHI to improve medicines access and use, systematic research is needed on medicine benefits and their performance, including the impacts of CHI on access to, affordability, and use of medicines at the household level.